Analysis of Limestone Magnetic Susceptibility Value as a Cement Manufacturing Material using Bartington Magnetic Susceptibility Meter - Yogi AlFajar; - Hamdi; - Syafriani; Fatni Mufit (PILLAR OF PHYSICS, 2023)
Limestone is the main ingredient for cement formation, 80% of the amount of Limestone used in cement formation, but there is very little research on Limestone, even though Limestone is very influential on the maximum compressive strength of cement. The purpose of this study was to obtain a new standard for cement based on the abundance of magnetic minerals indicated by the value of their Magnetic susceptibility, especially in Limestone which is the maining redientin cement manufacture, and also the lack of research on the susceptibility and types of minerals contained in Limestone. The method used in this study is a magnetic method where the magnetic susceptibility value of the sample is measured using a Magnetic Susceptibility Meter type MS2B. Limestone magnetic susceptibility value from PT. Semen Padang has a range of values from 17.6 x 10-8m3/kg to 90 x 10-8 m3/kg and has a dominant value, where Limestone has little or almost no Superparamagnetic grains, the reisonly one sample that has Superparamagnetic grains. Based on the range of magnetic susceptibility values obtained the magnetic properties of Limestone from PT. Semen Padang is Antiferromagnetic and has a type of magnetic mineral, namely Hematite